Reflexiones en torno al ciberacoso laboral en el Perú - Puntriano Rosas, César (2022)
Cyberbullying at work constitutes, undoubtedly, a form of violence exacerbated by the use of Information and Communication Technologies, of a multi-offensive nature as it involves an impairment of both unspecific and specifically labor fundamental rights. In this paper we reflect on its manifestations and the response formulated by the Peruvian labor law. For its preparation we have resorted to bibliographic research, through access to texts in English and Spanish that address cyberbullying. Likewise, the main conclusions point to rescuing how fundamental it is to adopt preventive measures, such as training staff on workplace about cyberbullying practices or how to avoid them, but also to commit the company's senior management. The level of response that the Peruvian legal system has is not optimal, since it does not require that companies implement procedures to prevent and punish acts of cyberbullying at work, however it is part of the employer’s duties the adoption of corresponding preventive mechanisms, safeguarding the rights of those involved. Ideally, this type of mechanism should have the participation of trade union organizations, but given the low unionization rate that exists in Peru, this could not be taken as a rule. However, a committee could even be formed with representation from the personnel that will be in charge of the investigation to provide impartiality to the procedure.